The evolution of sustainability discourses in online reviews: an investigation of the impact of triple bottom line dimensions on tourists’ eWOM and destination satisfaction. - David D'Acunto; Serena Lonardi; Ilenia Confente (2024)
Although sustainable tourism is a widely used paradigm, research has mainly focused on the supply side and on the environmental dimension. The research about sustainability in tourism, with particular regard to socio-economic and cultural dimensions, is still scant, especially regarding how these dimensions are perceived by tourists. Our research aims at filling that gap by examining to what extent international and local travelers visiting a destination that is to some extent suffering from overtourism engage in discussing online environmental, socio-economic, and cultural aspects of sustainability when reviewing online. We selected the destination of Iceland collecting 325,000 TripAdvisor reviews of 1445 Iceland attractions covering a ten-year time-frame (2013-2023) were analyzed through text analytics, combining a few specific dictionaries developed to study the online communication of sustainable tourism, CSR communication, and consumer sentiment. Combining text analytics with correlation and regression analysis, the findings reveal an increasing trend in tourists’ attention to socio-economic aspects of sustainability (e.g., discussions about employees, human rights, community) while a decreasing trend with regard to the environmental aspects over time. Interestingly, tourists discussing socio-economic and cultural aspects reflect a more positive sentiment polarity in their reviews, while reviews focusing on environmental aspects being correlated with negative emotions. In addition, results from the regression analysis shows how socio-economic and cultural framed reviews positively relate to ratings, while environmentally framed reviews negatively relate to ratings. Destinations are thus suggested to increase their attention and communication toward the socio-economic and cultural aspects of their attraction to enhance customer satisfaction online.